Effect of Calcium ion on the interaction between Thrombin and Heparin. Thermal Denaturation - Machovich, Raymund; Arányi, Péter (Thrombosis and Haemostasis, 1977)
Heat inactivation of thrombin at 54° C followed first order kinetics with a rate constant of 1.0 min−1 approximately. Addition of heparin resulted in protection against thermal denaturation and, at the same time, rendered denaturation kinetics more complex. Analysis of the biphasic curve of heat inactivation in the presence of heparin revealed that the rate constants of the second phase changed systematically with heparin concentrations. Namely, at 4.5 × 10−6M, 9 × 10−6M, 1.8 × 10−5M and 3.6 × 10−5M heparin concentrations, the rate constants were 0.27 min−1, 0.17 min−1, 0.11 min−1 and 0.06 min−1, respectively.Sulfate as well as phosphate ions displayed also enzyme protection against heat inactivation, however, the same effect was obtained already at a heparin concentration, lower by three orders of magnitude.The kinetics of enzyme denaturation was not affected by calcium ions, whereas in the presence of heparin the inactivation rate of thrombin changed, i. e. calcium ions abolished the biphasic character of time course of thermal denaturation.Thus, the data suggest that calcium ions contribute to the effect of heparin on thrombin.